EDITORIAL - Leiros Sarmento da Silva, Iasmin; Rocha, Maria Clara Rodrigues; Rossinetti Rufinoni, Priscila (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2019)
Editorial do volume 07, número 14, ano 2018.